Fiber reinforced hydrogel as well as preparation method and application thereof
Fiber-reinforced hydrogels were prepared by acidification and cross-linking reactions, which solved the problem of low mechanical strength of hydrogels and achieved the effects of high strength, long service life and reduced cost.
Patent Information
- Application Number
- CN202411486668.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-10
AI Technical Summary
The existing three-dimensional network structure of hydrogels is filled with a large amount of water and polyols, resulting in low mechanical strength and easy tearing and deformation.
A fiber-reinforced hydrogel preparation method was adopted, in which sodium carboxymethyl cellulose fibers were acidified to form hydrogen carboxymethyl cellulose fibers, and then crosslinked with aluminum hydroxyl crosslinking agent in an acidic environment to enhance the mechanical strength of the hydrogel.
The prepared fiber-reinforced hydrogel has high strength, good water retention, long service life, and is skin-friendly and comfortable when applied to the body. It also reduces production costs and improves the competitiveness of medical dressings.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical hydrogels, and in particular relates to a fiber-reinforced hydrogel and a preparation method and application thereof. Background Art
[0002] Polymer hydrogel is a multi-component system composed of a three-dimensional cross-linked polymer network structure and water. It can swell in water and retain a large amount of water without dissolving. Hydrogel has good hydrophilicity and biocompatibility. In recent years, it has been widely used in medicine, cosmetics, industrial products, agriculture and other fields. Among the many hydrogel products, one of the most representative products is the fever-reducing patch. Traditional physical fever-reducing methods include ice pack cooling, water towel application, and body rubbing, but these methods have disadvantages such as inconvenience in use. Polymer hydrogel fever-reducing patches use polymer hydrogel as the matrix, load a large amount of water and a small amount of natural cooling agent into the polymer gel, absorb heat through the evaporation of water, and take away the heat generated by the human body when it has a fever, thereby achieving the effect of cooling and reducing fever.
[0003] Another representative hydrogel product is hydrogel dressing. Wounds can be defined as skin defects caused by mechanical, electrical, thermal, chemical and other factors or caused by physiological abnormalities. At present, a new wound care theory, the moist healing theory, has emerged at home and abroad. Under the influence of this theory, new moisturizing dressings have also emerged, bringing new methods for wound care. Hydrogel dressings are a type of moisturizing dressing and have been widely used in clinical practice.
[0004] However, due to the three-dimensional network structure of the hydrogel, which is filled with a large amount of water and polyols, the mechanical strength of the hydrogel is not high, and it is easy to tear and deform during use. Therefore, a method for improving the strength of the hydrogel is urgently needed. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a fiber-reinforced hydrogel and a preparation method and application thereof, so as to achieve the purpose of the invention of improving the strength of the hydrogel.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: One of the purposes of the present invention is to provide a fiber-reinforced hydrogel. The raw materials of the hydrogel are, by weight, 21 to 23 parts of glycerol, 5 to 6 parts of partially neutralized sodium polyacrylate, 0.5 to 10 parts of mixed fiber, 70 to 75 parts of water, 0.22 to 0.25 parts of tartaric acid, 0.11 to 0.15 parts of aluminum glycolate and 0.1 to 0.13 parts of disodium ethylenediaminetetraacetate.
[0007] The second object of the present invention is to provide a method for preparing a fiber-reinforced hydrogel, the preparation method comprising the following steps: S1, acidification The sodium carboxymethyl cellulose fiber is added into an acid composite solution and immersed for acidification treatment to remove a portion of the sodium in the sodium carboxymethyl cellulose fiber, and then filtered to obtain a mixed fiber of the sodium carboxymethyl cellulose fiber and the carboxymethyl cellulose hydrogen fiber.
[0008] Preferably, in terms of mass fraction, the alcohol in the acid composite solution accounts for 65-75%, the acid accounts for 1-4.5%, and the rest is water. Sodium carboxymethyl cellulose fiber is soluble in water, so in order to prevent the sodium carboxymethyl cellulose fiber from dissolving, the alcohol concentration in the acid composite solution should be greater than 65%; but too high an alcohol concentration will hinder sodium removal, and the alcohol preferably accounts for 65-75%.
[0009] Preferably, the alcohol is one or more of methanol, ethanol and isopropanol.
[0010] Preferably, the acid is one or more of acetic acid and hydrochloric acid.
[0011] Preferably, the acidification treatment time is 4 to 24 hours.
[0012] Preferably, the proportion of carboxymethyl cellulose hydrogen fibers in the mixed fibers is greater than 70wt%, and the rest is sodium carboxymethyl cellulose fibers.
[0013] Preferably, the length of the sodium carboxymethyl cellulose fiber is 0.1 to 4 mm, and the fineness is 1 to 5 dtex.
[0014] Preferably, the mass ratio of the sodium carboxymethyl cellulose fiber to the acid composite solution is 1:10-40.
[0015] Sodium carboxymethyl cellulose fiber is a fibrous cellulose ether with higher hydrophilicity and water solubility, which is made of cellulose fiber and regenerated cellulose fiber through alkalization and etherification. However, sodium carboxymethyl cellulose fiber is soluble in water. If it is made into hydrogel, it will dissolve in water during the preparation process and cannot maintain the original fiber structure, which cannot achieve the purpose of subsequent strengthening of hydrogel. Therefore, it can be further acidified to form carboxymethyl cellulose hydrogen fiber, which will serve as the basis for the subsequent cross-linking reaction with trivalent aluminum ions. Sodium carboxymethyl cellulose fiber is too small, and the prepared carboxymethyl cellulose hydrogen fiber has no obvious strengthening effect on hydrogel. Sodium carboxymethyl cellulose fiber is too large, and the generated carboxymethyl cellulose hydrogen fiber will affect the morphology of hydrogel. Therefore, the length of sodium carboxymethyl cellulose fiber is preferably 0.1-4 mm, and the fineness is preferably 1-5 dtex.
[0016] The concentration of the acid composite solution and the acid treatment time affect the formation of carboxymethyl cellulose hydrogen fibers. Too high acid concentration and too long acid treatment time will cause cellulose degradation. Low acid concentration and short acid treatment time will cause insufficient carboxymethyl cellulose hydrogen fiber production. Control the concentration of the acid composite solution and the acid treatment time to ensure that carboxymethyl cellulose hydrogen fibers account for more than 70wt% of the mixed fibers.
[0017] S2. Preparation of oil phase Add glycerin to a whisk, then add part of the neutralized sodium polyacrylate and mixed fiber, start stirring, and stir until it becomes a paste-like semi-fluid state to obtain the oil phase.
[0018] Preferably, the partially neutralized sodium polyacrylate is a mixture of polyacrylic acid and sodium polyacrylate.
[0019] S3. Preparation of aqueous phase Add water, tartaric acid, aluminum glycolate and disodium ethylenediaminetetraacetate into a stirrer and stir. After stirring, let stand to defoam to obtain a water phase.
[0020] Preferably, the agitator is a vacuum double planetary power agitator, and the stirring time is 10 to 20 minutes.
[0021] S4. Preparation of hydrogel The oil phase is added into the water phase and stirred to mix the two, and then the stirring is continued for 5 to 8 minutes under vacuum conditions, and the vacuum is released to discharge the mixture of the oil phase and the water phase to obtain a fiber-reinforced hydrogel.
[0022] Preferably, the vacuum degree of the vacuum condition is 0.05-0.15 MPa.
[0023] In the preparation process of hydrogel, partially neutralized sodium polyacrylate and carboxymethyl cellulose hydrogen fiber are first dispersed in glycerol to form an oil phase; water, disodium ethylenediaminetetraacetic acid, tartaric acid, and aluminum glycolate crosslinking agent form an aqueous phase, wherein disodium ethylenediaminetetraacetic acid is a metal ion chelating agent to promote more uniform crosslinking, and tartaric acid provides an acidic environment. During blending, carboxymethyl cellulose hydrogen fiber swells in water, and under acidic conditions, partially neutralized sodium polyacrylate and carboxymethyl cellulose hydrogen fiber in the oil phase undergo crosslinking reaction with aluminum glycolate crosslinking agent to form a swollen and water-insoluble fiber-reinforced three-dimensional mesh colloid, thereby achieving the purpose of enhancing the strength of the hydrogel.
[0024] Control the dosage of aluminum glycolate crosslinking agent. When there is too much aluminum glycolate crosslinking agent, the crosslinked network structure in the hydrogel is dense, and the hydrogel becomes "brittle", resulting in a decrease in strength. When there is too little aluminum glycolate crosslinking agent, the crosslinked network structure in the hydrogel is insufficient, and the strength enhancement of the hydrogel is not obvious.
[0025] The third object of the present invention is to provide an application of a fiber-reinforced hydrogel, the application comprising: The fiber-reinforced hydrogel is transported to a coating device, coated on a non-woven fabric, and then subjected to a aging treatment to obtain a hydrogel dressing.
[0026] Preferably, the coating thickness is 0.5 to 7 mm; and the aging treatment time is 8 to 24 hours.
[0027] Due to the adoption of the above technical solution, the technical effects achieved by the present invention are: 1. The fiber-reinforced hydrogel prepared by the present invention has high strength and good water-holding effect. After being made into a dressing, it can be used for a long time, is skin-friendly and comfortable to apply, and is easy to use.
[0028] 2. Partially neutralized sodium polyacrylate is expensive, while sodium carboxymethyl cellulose fiber is cheap. Adding carboxymethyl cellulose hydrogen fiber to the raw materials of hydrogel and reducing the amount of sodium polyacrylate can significantly reduce production costs and improve core competitiveness in the field of medical dressings.
[0029] 3. After the fiber-reinforced hydrogel prepared by the present invention is made into a dressing, the tensile strength is measured to be 1.53-4.62 MPa, which has high strength and is not easy to tear or deform. DETAILED DESCRIPTION
[0030] The present invention is further described below in conjunction with specific embodiments.
[0031] Example 1 A fiber-reinforced hydrogel comprises, by weight, 22 parts of glycerol, 5.5 parts of partially neutralized sodium polyacrylate, 6 parts of mixed fiber, 73 parts of water, 0.23 parts of tartaric acid, 0.13 parts of aluminum glycolate and 0.12 parts of disodium ethylenediaminetetraacetate.
[0032] The preparation method of the fiber-reinforced hydrogel comprises the following steps: S1, acidification The sodium carboxymethyl cellulose fiber is added into an acid composite solution and immersed for acidification treatment to remove a portion of the sodium in the sodium carboxymethyl cellulose fiber, and then filtered to obtain a mixed fiber of the sodium carboxymethyl cellulose fiber and the carboxymethyl cellulose hydrogen fiber.
[0033] In terms of mass fraction, the acid composite solution comprises 70% alcohol, 2.5% acid and the rest water.
[0034] The alcohol is ethanol, and the acid is hydrochloric acid.
[0035] The acidification treatment time is 12h.
[0036] The mixed fibers contain 80 wt% of carboxymethyl cellulose hydrogen fibers and the rest are carboxymethyl cellulose sodium fibers.
[0037] The length of the sodium carboxymethyl cellulose fiber is 2 mm, and the fineness is 3 dtex.
[0038] The mass ratio of the sodium carboxymethyl cellulose fiber to the acid composite solution is 1:20.
[0039] S2. Preparation of oil phase Add glycerin to a whisk, then add part of the neutralized sodium polyacrylate and mixed fiber, start stirring, and stir until it becomes a paste-like semi-fluid state to obtain the oil phase.
[0040] The partially neutralized sodium polyacrylate is a mixture of polyacrylic acid and sodium polyacrylate.
[0041] S3. Preparation of aqueous phase Add water, tartaric acid, aluminum glycolate and disodium ethylenediaminetetraacetate into a stirrer and stir. After stirring, let stand to defoam to obtain a water phase.
[0042] The stirrer is a vacuum double planetary power stirrer, and the stirring time is 15 minutes.
[0043] S4. Preparation of hydrogel The oil phase is added to the water phase and stirred to mix the two, and then the stirring is continued for 7 minutes under vacuum conditions. The vacuum is released and the mixture of the oil phase and the water phase is discharged to obtain a fiber-reinforced hydrogel.
[0044] The vacuum degree of the vacuum condition is 0.1 MPa.
[0045] Applications of the fiber-reinforced hydrogel include: The fiber-reinforced hydrogel is transported to a coating device, coated on a non-woven fabric, and then subjected to a aging treatment to obtain a hydrogel dressing.
[0046] The coating thickness is 2.5 mm; the aging treatment time is 16 h.
[0047] Example 2 A fiber-reinforced hydrogel comprises, by weight, 21 parts of glycerol, 6 parts of partially neutralized sodium polyacrylate, 0.5 parts of mixed fiber, 70 parts of water, 0.22 parts of tartaric acid, 0.15 parts of aluminum glycolate and 0.13 parts of disodium ethylenediaminetetraacetate.
[0048] The preparation method of the fiber-reinforced hydrogel comprises the following steps: S1, acidification The sodium carboxymethyl cellulose fiber is added into an acid composite solution and immersed for acidification treatment to remove a portion of the sodium in the sodium carboxymethyl cellulose fiber, and then filtered to obtain a mixed fiber of the sodium carboxymethyl cellulose fiber and the carboxymethyl cellulose hydrogen fiber.
[0049] In terms of mass fraction, the acid composite solution comprises 65% alcohol, 1% acid and the rest water.
[0050] The alcohol is methanol, and the acid is acetic acid.
[0051] The acidification treatment time is 24h.
[0052] The mixed fibers include 71 wt% carboxymethyl cellulose hydrogen fibers and the rest are carboxymethyl cellulose sodium fibers.
[0053] The length of the sodium carboxymethyl cellulose fiber is 0.1 mm, and the fineness is 1 dtex.
[0054] The mass ratio of the sodium carboxymethyl cellulose fiber to the acid composite solution is 1:10.
[0055] S2. Preparation of oil phase Add glycerin to a whisk, then add part of the neutralized sodium polyacrylate and mixed fiber, start stirring, and stir until it becomes a paste-like semi-fluid state to obtain the oil phase.
[0056] The partially neutralized sodium polyacrylate is a mixture of polyacrylic acid and sodium polyacrylate.
[0057] S3. Preparation of aqueous phase Add water, tartaric acid, aluminum glycolate and disodium ethylenediaminetetraacetate into a stirrer and stir. After stirring, let stand to defoam to obtain a water phase.
[0058] The stirrer is a vacuum double planetary power stirrer, and the stirring time is 10 minutes.
[0059] S4. Preparation of hydrogel The oil phase is added to the water phase and stirred to mix the two, and then the stirring is continued for 5 minutes under vacuum conditions. The vacuum is released and the mixture of the oil phase and the water phase is discharged to obtain a fiber-reinforced hydrogel.
[0060] The vacuum degree of the vacuum condition is 0.05 MPa.
[0061] Applications of the fiber-reinforced hydrogel include: The fiber-reinforced hydrogel is transported to a coating device, coated on a non-woven fabric, and then subjected to a aging treatment to obtain a hydrogel dressing.
[0062] The coating thickness is 0.5 mm; the aging treatment time is 8 h.
[0063] Example 3 A fiber-reinforced hydrogel comprises, by weight, 23 parts of glycerol, 5 parts of partially neutralized sodium polyacrylate, 10 parts of mixed fiber, 75 parts of water, 0.25 parts of tartaric acid, 0.15 parts of aluminum glycolate and 0.13 parts of disodium ethylenediaminetetraacetate.
[0064] The preparation method of the fiber-reinforced hydrogel comprises the following steps: S1, acidification The sodium carboxymethyl cellulose fiber is added into an acid composite solution and immersed for acidification treatment to remove a portion of the sodium in the sodium carboxymethyl cellulose fiber, and then filtered to obtain a mixed fiber of the sodium carboxymethyl cellulose fiber and the carboxymethyl cellulose hydrogen fiber.
[0065] In terms of mass fraction, the acid composite solution comprises 75% alcohol, 4.5% acid and the rest water.
[0066] The alcohol is isopropanol, and the acid is acetic acid.
[0067] The acidification treatment time is 4 hours.
[0068] The mixed fibers include 76 wt % carboxymethyl cellulose hydrogen fibers and the rest are carboxymethyl cellulose sodium fibers.
[0069] The length of the sodium carboxymethyl cellulose fiber is 4 mm, and the fineness is 5 dtex.
[0070] The mass ratio of the sodium carboxymethyl cellulose fiber to the acid composite solution is 1:40.
[0071] S2. Preparation of oil phase Add glycerin to a whisk, then add part of the neutralized sodium polyacrylate and mixed fiber, start stirring, and stir until it becomes a paste-like semi-fluid state to obtain the oil phase.
[0072] The partially neutralized sodium polyacrylate is a mixture of polyacrylic acid and sodium polyacrylate.
[0073] S3. Preparation of aqueous phase Add water, tartaric acid, aluminum glycolate and disodium ethylenediaminetetraacetate into a stirrer and stir. After stirring, let stand to defoam to obtain a water phase.
[0074] The stirrer is a vacuum double planetary power stirrer, and the stirring time is 20 minutes.
[0075] S4. Preparation of hydrogel The oil phase is added to the water phase and stirred to mix the two, and then the stirring is continued for 8 minutes under vacuum conditions. The vacuum is released and the mixture of the oil phase and the water phase is discharged to obtain a fiber-reinforced hydrogel.
[0076] The vacuum degree of the vacuum condition is 0.15 MPa.
[0077] Applications of the fiber-reinforced hydrogel include: The fiber-reinforced hydrogel is transported to a coating device, coated on a non-woven fabric, and then subjected to a aging treatment to obtain a hydrogel dressing.
[0078] The coating thickness is 7 mm; the aging time is 24 h.
[0079] Example 4 A fiber-reinforced hydrogel comprises, by weight, 22 parts of glycerol, 5.5 parts of partially neutralized sodium polyacrylate, 2 parts of mixed fiber, 73 parts of water, 0.23 parts of tartaric acid, 0.12 parts of aluminum glycolate and 0.12 parts of disodium ethylenediaminetetraacetate.
[0080] The preparation method of the fiber-reinforced hydrogel comprises the following steps: S1, acidification The sodium carboxymethyl cellulose fiber is added into an acid composite solution and immersed for acidification treatment to remove a portion of the sodium in the sodium carboxymethyl cellulose fiber, and then filtered to obtain a mixed fiber of the sodium carboxymethyl cellulose fiber and the carboxymethyl cellulose hydrogen fiber.
[0081] In terms of mass fraction, the acid composite solution comprises 70% alcohol, 2.5% acid and the rest water.
[0082] The alcohol is ethanol, and the acid is hydrochloric acid.
[0083] The acidification treatment time is 12h.
[0084] The mixed fibers contain 80 wt% of carboxymethyl cellulose hydrogen fibers and the rest are carboxymethyl cellulose sodium fibers.
[0085] The length of the sodium carboxymethyl cellulose fiber is 2 mm, and the fineness is 3 dtex.
[0086] The mass ratio of the sodium carboxymethyl cellulose fiber to the acid composite solution is 1:20.
[0087] S2. Preparation of oil phase Add glycerin to a whisk, then add part of the neutralized sodium polyacrylate and mixed fiber, start stirring, and stir until it becomes a paste-like semi-fluid state to obtain the oil phase.
[0088] The partially neutralized sodium polyacrylate is a mixture of polyacrylic acid and sodium polyacrylate.
[0089] S3. Preparation of aqueous phase Add water, tartaric acid, aluminum glycolate and disodium ethylenediaminetetraacetate into a stirrer and stir. After stirring, let stand to defoam to obtain a water phase.
[0090] The stirrer is a vacuum double planetary power stirrer, and the stirring time is 15 minutes.
[0091] S4. Preparation of hydrogel The oil phase is added to the water phase and stirred to mix the two, and then the stirring is continued for 7 minutes under vacuum conditions. The vacuum is released and the mixture of the oil phase and the water phase is discharged to obtain a fiber-reinforced hydrogel.
[0092] The vacuum degree of the vacuum condition is 0.1 MPa.
[0093] Applications of the fiber-reinforced hydrogel include: The fiber-reinforced hydrogel is transported to a coating device, coated on a non-woven fabric, and then subjected to a aging treatment to obtain a hydrogel dressing.
[0094] The coating thickness is 2.5 mm; the aging treatment time is 16 h.
[0095] Example 5 A fiber-reinforced hydrogel comprises, by weight, 22 parts of glycerol, 5.5 parts of partially neutralized sodium polyacrylate, 8 parts of mixed fiber, 73 parts of water, 0.24 parts of tartaric acid, 0.14 parts of aluminum glycolate and 0.12 parts of disodium ethylenediaminetetraacetate.
[0096] The preparation method of the fiber-reinforced hydrogel comprises the following steps: S1, acidification The sodium carboxymethyl cellulose fiber is added into an acid composite solution and immersed for acidification treatment to remove a portion of the sodium in the sodium carboxymethyl cellulose fiber, and then filtered to obtain a mixed fiber of the sodium carboxymethyl cellulose fiber and the carboxymethyl cellulose hydrogen fiber.
[0097] In terms of mass fraction, the acid composite solution comprises 70% alcohol, 2.5% acid and the rest water.
[0098] The alcohol is ethanol, and the acid is hydrochloric acid.
[0099] The acidification treatment time is 12h.
[0100] The mixed fibers contain 80 wt% of carboxymethyl cellulose hydrogen fibers and the rest are carboxymethyl cellulose sodium fibers.
[0101] The length of the sodium carboxymethyl cellulose fiber is 2 mm, and the fineness is 3 dtex.
[0102] The mass ratio of the sodium carboxymethyl cellulose fiber to the acid composite solution is 1:20.
[0103] S2. Preparation of oil phase Add glycerin to a whisk, then add part of the neutralized sodium polyacrylate and mixed fiber, start stirring, and stir until it becomes a paste-like semi-fluid state to obtain the oil phase.
[0104] The partially neutralized sodium polyacrylate is a mixture of polyacrylic acid and sodium polyacrylate.
[0105] S3. Preparation of aqueous phase Add water, tartaric acid, aluminum glycolate and disodium ethylenediaminetetraacetate into a stirrer and stir. After stirring, let stand to defoam to obtain a water phase.
[0106] The stirrer is a vacuum double planetary power stirrer, and the stirring time is 15 minutes.
[0107] S4. Preparation of hydrogel The oil phase is added to the water phase and stirred to mix the two, and then the stirring is continued for 7 minutes under vacuum conditions. The vacuum is released and the mixture of the oil phase and the water phase is discharged to obtain a fiber-reinforced hydrogel.
[0108] The vacuum degree of the vacuum condition is 0.1 MPa.
[0109] Applications of the fiber-reinforced hydrogel include: The fiber-reinforced hydrogel is transported to a coating device, coated on a non-woven fabric, and then subjected to a aging treatment to obtain a hydrogel dressing.
[0110] The coating thickness is 2.5 mm; the aging treatment time is 16 h.
[0111] Example 6 A fiber-reinforced hydrogel comprises, by weight, 22 parts of glycerol, 5.5 parts of partially neutralized sodium polyacrylate, 6 parts of mixed fiber, 73 parts of water, 0.23 parts of tartaric acid, 0.13 parts of aluminum glycolate and 0.12 parts of disodium ethylenediaminetetraacetate.
[0112] The preparation method of the fiber-reinforced hydrogel comprises the following steps: S1, acidification The sodium carboxymethyl cellulose fiber is added into an acid composite solution and immersed for acidification treatment to remove a portion of the sodium in the sodium carboxymethyl cellulose fiber, and then filtered to obtain a mixed fiber of the sodium carboxymethyl cellulose fiber and the carboxymethyl cellulose hydrogen fiber.
[0113] In terms of mass fraction, the acid composite solution comprises 70% alcohol, 2.5% acid and the rest water.
[0114] The alcohol is ethanol, and the acid is hydrochloric acid.
[0115] The acidification treatment time is 12h.
[0116] The mixed fibers contain 80 wt% of carboxymethyl cellulose hydrogen fibers and the rest are carboxymethyl cellulose sodium fibers.
[0117] The length of the sodium carboxymethyl cellulose fiber is 2 mm, and the fineness is 3 dtex.
[0118] The mass ratio of the sodium carboxymethyl cellulose fiber to the acid composite solution is 1:20.
[0119] S2. Preparation of oil phase Add glycerin to a whisk, then add part of the neutralized sodium polyacrylate and mixed fiber, start stirring, and stir until it becomes a paste-like semi-fluid state to obtain the oil phase.
[0120] The partially neutralized sodium polyacrylate is a mixture of polyacrylic acid and sodium polyacrylate.
[0121] S3. Preparation of aqueous phase Add water, tartaric acid, aluminum glycolate and disodium ethylenediaminetetraacetate into a stirrer and stir. After stirring, let stand to defoam to obtain a water phase.
[0122] The stirrer is a vacuum double planetary power stirrer, and the stirring time is 15 minutes.
[0123] S4. Preparation of hydrogel The oil phase is added to the water phase and stirred to mix the two, and then the stirring is continued for 7 minutes under vacuum conditions. The vacuum is released and the mixture of the oil phase and the water phase is discharged to obtain a fiber-reinforced hydrogel.
[0124] The vacuum degree of the vacuum condition is 0.1 MPa.
[0125] Applications of the fiber-reinforced hydrogel include: The fiber-reinforced hydrogel is transported to a coating device, coated on a non-woven fabric, and then subjected to a aging treatment to obtain a hydrogel dressing.
[0126] The coating thickness is 7 mm and the aging time is 16 h.
[0127] Comparative Example 1 Representative Example 1 was selected as Comparative Example 1, except for the mixed fibers in the hydrogel raw material, and the rest was the same as Example 1.
[0128] Comparative Example 2 Representative Example 1 was selected as Comparative Example 1, in which the mixed fibers in the hydrogel raw material were replaced with an equal amount of sodium carboxymethyl cellulose fibers, and the rest were the same as in Example 1.
[0129] The hydrogel dressings prepared in the examples and comparative examples were made into specimens with a width of 10 mm and a length of 20 mm, and their tensile strengths were measured. See Table 1 for details.
[0130] Table 1 Test items Tensile strength (MPa) Example 1 3.057 Example 2 1.53 Example 3 2.976 Example 4 2.041 Example 5 2.735 Example 6 4.62 Comparative Example 1 0.271 Comparative Example 2 0.293 It can be seen from Table 1 that the tensile strength of the embodiments is significantly better than that of the comparative examples; compared with Example 1, the amount of mixed fiber added in Example 4 is reduced, the degree of crosslinking is insufficient, and the tensile strength is reduced; compared with Example 1, the amount of mixed fiber added in Example 5 is increased, the crosslinking structure is too dense, and the hydrogel is "brittle", so the tensile strength is also reduced; compared with Example 1, the coating thickness in Example 6 is increased, and the strength of the hydrogel is increased, indicating that the degree of crosslinking of the fibers in the hydrogel and the thickness of the hydrogel have a greater impact on the hydrogel.
[0131] In Comparative Example 2, the mixed fiber in the hydrogel raw material was replaced with an equal amount of sodium carboxymethyl cellulose fiber, and the rest was consistent with Example 1. The tensile strength of the prepared hydrogel dressing was significantly lower than that of the example, and did not change much compared with Comparative Example 1, indicating that the sodium carboxymethyl cellulose fiber was soluble in water and had no obvious strengthening effect on the hydrogel.
[0132] Unless otherwise specified, the ratios and percentages described in the present invention are all weight ratios and weight percentages; and the raw materials are all commercially available.
[0133] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A fiber-reinforced hydrogel, characterized in that: According to weight percentage, the raw materials of the hydrogel are 21-23 parts of glycerol, 5-6 parts of partially neutralized sodium polyacrylate, 0.5-10 parts of mixed fiber, 70-75 parts of water, 0.22-0.25 parts of tartaric acid, 0.11-0.15 parts of aluminum glycolate and 0.1-0.13 parts of disodium ethylenediaminetetraacetate.
2. A method for preparing a fiber-reinforced hydrogel, characterized in that: The preparation method comprises acidification, preparation of an oil phase, preparation of a water phase and preparation of a hydrogel.
3. The method for preparing a fiber-reinforced hydrogel according to claim 2, characterized in that: The acidification is to add sodium carboxymethyl cellulose fibers into an acid composite solution and soak them for acidification treatment, and then obtain mixed fibers of sodium carboxymethyl cellulose fibers and hydrogen carboxymethyl cellulose fibers after filtering.
4. The method for preparing a fiber-reinforced hydrogel according to claim 3, characterized in that: In terms of mass fraction, the alcohol in the acid composite solution accounts for 65-75%, the acid accounts for 1-4.5%, and the rest is water; The alcohol is one or more of methanol, ethanol, and isopropanol; The acid is one or more of acetic acid and hydrochloric acid; The acidification treatment time is 4 to 24 hours.
5. The method for preparing a fiber-reinforced hydrogel according to claim 3, characterized in that: The proportion of carboxymethyl cellulose hydrogen fibers in the mixed fibers is greater than 70wt%, and the rest is carboxymethyl cellulose sodium fibers; The length of the sodium carboxymethyl cellulose fiber is 0.1 to 4 mm, and the fineness is 1 to 5 dtex; The mass ratio of the sodium carboxymethyl cellulose fiber to the acid composite solution is 1:10-40.
6. The method for preparing a fiber-reinforced hydrogel according to claim 2, characterized in that: The oil phase is prepared by adding glycerin into an egg beater, then adding part of the neutralized sodium polyacrylate and mixed fiber, starting stirring, and stirring until the mixture is in a paste-like and semi-fluid state to obtain the oil phase.
7. The method for preparing a fiber-reinforced hydrogel according to claim 2, characterized in that: The aqueous phase is prepared by adding water, tartaric acid, aluminum glycolate and disodium ethylenediaminetetraacetate into a stirrer and stirring, and after stirring, standing to defoam, to obtain an aqueous phase; The stirrer is a vacuum double planetary power stirrer, and the stirring time is 10 to 20 minutes.
8. The method for preparing a fiber-reinforced hydrogel according to claim 2, characterized in that: The preparation of the hydrogel is as follows: adding the oil phase into the water phase and stirring to mix the two, then continuing to stir for 5 to 8 minutes under vacuum conditions, releasing the vacuum, and discharging the mixture of the oil phase and the water phase to obtain the fiber-reinforced hydrogel; The vacuum degree of the vacuum condition is 0.05-0.15 MPa.
9. Use of a fiber-reinforced hydrogel prepared by the method for preparing a fiber-reinforced hydrogel according to any one of claims 2 to 9, characterized in that: Applications of the fiber-reinforced hydrogel include: The fiber-reinforced hydrogel is transported to a coating device, coated on a non-woven fabric, and then subjected to a aging treatment to obtain a hydrogel dressing.
10. The use of a fiber-reinforced hydrogel according to claim 9, characterized in that: The coating thickness is 0.5 to 7 mm; the aging treatment time is 8 to 24 hours.